PARACOCCIDIOIDOMYCOSIS DUE TO SMALL FORMS OF Paracoccidioides. A REPORT OF 12 CASES AND REVIEW OF THE LITERATURE - Guimarães Coelho, Mariana; Bittencourt Severo, Cecília; de Mattos Oliveira, Flávio; Carlos Severo, Luiz (Revista de Patologia Tropical / Journal of Tropical Pathology, 2016)
Paracoccidioidomycosis (PCM) is a systemic mycosis with a geographic distribution limited to Latin America. PCM is caused by species in the genus Paracoccidioides, which usually appear in tissues as large yeasts, 5 to 30 ?m in size. The daughter cells are attached to the parent cell by a narrow neck. Sometimes smaller forms occur (1 to 4 ?m). These can be confused with other fungi, such as Histoplasma capsulatum and unencapsulated Cryptococcus variants. Twelve cases of PCM were reported with small forms of Paracoccidioides. The aim of this paper is to focus on the possibility of differential diagnosis with other systemic mycoses.